Vie et œuvre d’Eugène Poilane (1888-1964) - Ariadna Burgos; Benoît Carré (Revue d'ethnoécologie)
This article presents the life and work of Eugène Poilane (1888-1964), prospector, planter and explorer during the first half of the 20th century in French Indochina. The scientific legacy of E. Poilane is built around a series of manuscripts and a remarkable natural history collection deposited at the Muséum national d'Histoire naturelle in Paris (MNHN). The 50,000 botanical specimens kept at the French National Herbarium undoubtedly represent the most visible part of his work. The abundance and diversity of his collections reflect the exceptional life he led in Indochina: rigorous, exhaustive and very meticulous in his samplings, E. Poilane surveyed many regions that were rarely visited or even completely unknown to naturalists. He was interested in the local and documented indigenous knowledge, uses and methods of exploitation of the local flora, while drawing a very precise portrait of the life, customs and colonial spirit of the time. He spent over half a century in Indochina and, was able to fit in well in the society, even embodying some of its most tragic upheavals. His various observations, mostly unpublished, can be found on the labels of his herbarium specimens, in his notebooks, as well as in a set of manuscripts and correspondence which he bequeathed to the MNHN. Eugène Poilane is one of those traditional great naturalist explorers whose scientific work is at the crossroads of many fields of study such as ethnography, botany, soil science, ecology and agronomy. A simple, uneducated soldier, Poilane was spotted by Auguste Chevalier in 1918; 36 years later, Chevalier wrote about him: "It shall be one of the greatest prides of my life was to have discovered, one day in Indochina, this intrepid researcher and to have made him my disciple". In this article, we will illustrate part of this extraordinary naturalist's journey and his contribution to academic knowledge and to the understanding of the French colonial empire context in Indochina. The second article, which follows on from this one, illustrates the use of E. Poilane's scientific work in the study of mangroves in Vietnam.